Spatiality, sovereignty and Carl Schmitt geographies of the nomos - Legg, Stephen; T&F eBooks (Milton, Park, Abingdon, Oxon ; New York : Routledge, 2011)
"The writings of Carl Schmitt (1888-1985) are now indissociable from both an historical period and a contemporary moment. He will forever be remembered for his association with the National Socialists of 1930s Germany, and as the figure whose writings on sovereignty, politics, and the law provided justification for authoritarian, decisional states. Yet at the same time, the post-September 2001 world is one in which a wide range of scholars have increasingly turned to Schmitt to understand a world of "with us or against us" Manichaeism, spaces of exception which seem to be placed outside the law by legal mechanisms themselves, and the contestation of a uni-polar, post-1989 world. This attention marks out Schmitt as one of the foremost emerging theorists in critical theory and assures his work a large and growing audience. The aim of this book is to bring together geographers, and Schmitt experts who are attuned to the spatial dimensions of his work, to discuss The Nomos of the Earth in the International Law of the Jus Publicum Europaeum (Schmitt, 1950 [2003]). This longest of Schmitts published works saw him expand his interests from domestic to international law"--
pt. 1. Positions and concepts : Schmitt translations -- pt. 2. Historical geographies of the nomos -- pt. 3. Analytical geographies of the nomos -- pt. 4. Responses to the Nomos.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Schmitt, Carl, -- 1888-1985.; Schmitt, Carl, -- 1888-1985.; International relations; Political science -- Philosophy; Geopolitics; Electronic books